LAYANAN PENGUASAAN KONTEN MENGGUNAKAN MEDIA AUDIO VISUAL UNTUK MENINGKATKAN PEMAHAMAN KESEHATAN ORGAN REPRODUKSI REMAJA - Sudarmadi, Aris; Zamroni, Edris; Mahardika, Nur (Universitas Muria Kudus, 2023)
The aims of this study were: to find out the implementation of content mastery service activities in group guidance by using audio-visual media to increase understanding of adolescent reproductive health at Karang Taruna Tasikagung; to obtain the results of improving content mastery services in group guidance by using audio-visual media in increasing understanding of adolescent reproductive health at Karang Taruna Tasikagung. The results of the study show that the implementation of the service is carried out in five meetings. In the meeting there were still respondents who had not been able to adopt a healthy lifestyle and there were those who had adopted a healthy lifestyle and some respondents paid close attention; There are differences in the results of understanding reproductive health before and after providing services with content using audio-visual media. This means that content mastery services using audio-visual media can increase understanding of the reproductive health of youth at the Tasikagung.